2006
DOI: 10.1056/nejmoa054693
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Patients Treated with Natalizumab for Progressive Multifocal Leukoencephalopathy

Abstract: Background Progressive multifocal leukoencephalopathy (PML) was reported to have developed in three patients treated with natalizumab. We conducted an evaluation to determine whether PML had developed in any other treated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
392
0
8

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 718 publications
(402 citation statements)
references
References 13 publications
2
392
0
8
Order By: Relevance
“…A subsequent retrospective review of 3,417 patients who had received natalizumab found no cases of detectable JCV DNA in the cerebrospinal fluid and only 1 possible case of PML, which was unconfirmed due to lack of followup data; the estimated risk of PML in patients treated with natalizumab was 1 case per 1,000 patients in 18 months (71). The mechanisms underlying the involvement of natalizumab in the pathogenesis of PML remain unclear at present.…”
Section: Polyomavirusmentioning
confidence: 99%
“…A subsequent retrospective review of 3,417 patients who had received natalizumab found no cases of detectable JCV DNA in the cerebrospinal fluid and only 1 possible case of PML, which was unconfirmed due to lack of followup data; the estimated risk of PML in patients treated with natalizumab was 1 case per 1,000 patients in 18 months (71). The mechanisms underlying the involvement of natalizumab in the pathogenesis of PML remain unclear at present.…”
Section: Polyomavirusmentioning
confidence: 99%
“…Immune reconstitution as an effective approach to control of PML has been further established by the important experience of treating PML associated with natalizumab therapy in the setting of multiple sclerosis. Natalizumab-associated PML emerged in 2005 when this effective integrin inhibitor was found to increase vastly the risk of developing PML in a population that had previously never seen this complication [57][58][59][60]. Rapid immune reconstitution can be accomplished by using plasma exchange to speed drug clearance and allowing access to the brain for the existing immune response.…”
Section: Progressive Multifocal Leukencephalopathymentioning
confidence: 99%
“…Subsequently, evaluation of another patient who died in a trial for the treatment of Crohn's disease confirmed a third case of PML. With a known denominator of approximately 3,000 patients who received the drug during clinical trials to treat MS or Crohn's disease it was possible to estimate a rate of PML in patients who received natazilumab of approximately 1/1,000 (16,17). Because of the small number of PML cases it was not possible to definitively determine the relative contribution to risk by concomitant treatment with IFN β-1a or other immunosuppressive drugs.…”
Section: Natalizumab and Progressive Multifocal Leukoencephalopathy (mentioning
confidence: 99%